Towards psychedelic apprenticeship: Developing a gentle touch for the mediation and validation of psychedelic-induced insights and revelations. (October 2022) - Timmermann, Christopher; Watts, Rosalind; Dupuis, David
A striking feature of psychedelics is their ability to increase attribution of truth and meaningfulness to specific contents and ideas experienced, which may persist long after psychedelic effects have subsided. We propose that processes underlying conferral of meaning and truth in psychedelic experiences may act as a double-edged sword: while these may drive important therapeutic benefits, they also raise important considerations regarding the validation and mediation of knowledge gained during these experiences. Specifically, the ability of psychedelics to induce noetic feelings of revelation may enhance the significance and attribution of reality to specific beliefs, worldviews, and apparent memories which might exacerbate the risk of iatrogenic complications that other psychotherapeutic approaches have historically faced, such as false memory syndrome. These considerations are timely, as the use of psychedelics is becoming increasingly mainstream, in an environment marked by the emergence of strong commercial interest for psychedelic therapy. We elaborate on these ethical challenges via three examples illustrating issues of validation and mediation in therapeutic, neo-shamanic and research contexts involving psychedelic use. Finally, we propose a pragmatic framework to attend to these challenges based on an ethical approach which considers the embeddedness of psychedelic experiences within larger historical and cultural contexts, their intersubjective character and the use of practices which we conceptualise here as forms of psychedelic apprenticeship . This notion of apprenticeship goes beyond current approaches of preparation and integration by stressing the central importance of validation practices based on empathic resonance by an experienced therapist or guide.